Implementation of an online collaborative learning through grid portal technology - Zakaria, Nur Liyana (2010)
Individual work is significant in any learning course but, student should also learn the collaborative behavior. Students’ involvements are required in group attempt. Group works in designing and authoring a courseware is not an easy task. The purpose of this study is to identify student’s difficulties in completing their authoring activity or collaborative work in conventional environment. This study was conducted to design and develop an online collaborative tool through grid portal technology. UTM Grid Portal is developed for students of Faculty of Education to accomplish their courseware development project. Students engaged in collaborative learning might use blog as a medium to discuss with group members in order to gather information sharing ideas and distributing task. The evaluation process was conducted to obtain students engagement and involvement in collaborative environment activity. The study sample consisted of 36 undergraduate students enrolled in SPM 2332 (Authoring Language) course. Data was gathered using qualitative approach which was through blog discussion as a link in UTM Grid Portal. Result from the analysis shows that student’s activity in group work can be divided into three main categories which are cooperative and collaborative, support as well as task distribution. Cooperative and collaborative in students activity involves sharing ideas, sharing information, sharing problem as well as opinion and suggestion. Besides that, students support other group members by giving motivation, updating progress and show respect to others.